2007
DOI: 10.1302/0301-620x.89b10.19120
|View full text |Cite
|
Sign up to set email alerts
|

Association between radiological findings and symptoms at the patellofemoral joint in advanced knee osteoarthritis

Abstract: We investigated the association between the radiological findings and the symptoms arising from the patellofemoral joint in advanced osteoarthritis (OA) of the knee. Four radiological features, joint space narrowing, osteophyte formation, translation of the patella and focal attrition were assessed in 151 consecutive osteoarthritic knees in 107 patients undergoing total knee replacement. The symptoms which were assessed included anterior knee pain which was scored, the ability to rise from a chair and climb st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In our study, 7 patients had lateral subluxation of the patella on the preoperative skyline radiographs, and this was a highly significant predictor of poor outcome. Chang et al (2007) found that lateral patellar translation of the patella and difficulty in rising from a chair was predictive of increased anterior knee pain in osteoarthritic knees after total knee replacement. They suggested that patellofemoral malaligment and abnormal tracking may be an important cause of postoperative pain.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, 7 patients had lateral subluxation of the patella on the preoperative skyline radiographs, and this was a highly significant predictor of poor outcome. Chang et al (2007) found that lateral patellar translation of the patella and difficulty in rising from a chair was predictive of increased anterior knee pain in osteoarthritic knees after total knee replacement. They suggested that patellofemoral malaligment and abnormal tracking may be an important cause of postoperative pain.…”
Section: Discussionmentioning
confidence: 95%
“…Although patellar malalignment is considered to be a feature of patellofemoral joint pain in younger populations (14, 15), no studies have investigated whether people with patellofemoral joint OA have malaligned patellae. However, recent research has identified that patellar malalignment is associated with indices of patellofemoral joint OA (JSN and loss of cartilage thickness) (16–18), increased risk of progression of OA (greater JSN) (19), and greater symptom severity (20, 21). Furthermore, patellar malalignment is typically observed in a lateral direction (displacement or tilt), which likely reflects the OA disease process predominantly affecting the lateral patellofemoral joint compartment (22).…”
Section: Introductionmentioning
confidence: 99%
“… 24 Patellofemoral malalignment has been linked to symptom severity among older people with knee OA, although results are inconsistent. 2 , 19 Thus, while there is literature suggesting that patellofemoral malalignment may be related to magnetic resonance imaging (MRI)–defined structural features of patellofemoral OA (eg, osteophytes and cartilage defects) among people with PFP, this relationship and the potential relationship with symptoms (ie, pain and function) are currently unknown. Therefore, the aim of this study was to determine whether patellofemoral joint alignment and bony shape are associated with (1) cartilage, bone, and soft tissue morphological abnormalities defined on MRI and (2) patient characteristics and reported symptoms among people with PFP.…”
mentioning
confidence: 99%